Integrasi Nilai Aswaja dalam Promosi Kesehatan Mental Berbasis Komunitas Perspektif Holistik Maqasid Al-Syariah - Sri Muryati; Rahmawati Husain; Karmila Wijiati; Faiz Karim Fatkhullah (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
This study examines the integration of Ahlussunnah wal Jamaah (Aswaja) values in community-based mental health promotion through the holistic perspective of maqasid al-shariah. The phenomenon of increasing prevalence of mental health disorders in Indonesia, particularly among adolescents and young adults, requires a comprehensive approach that focuses not only on biomedical aspects but also considers the spiritual and socio-cultural dimensions of society. Aswaja values comprising tawasuth (moderation), tawazun (balance), tasamuh (tolerance), and i'tidal (justice) offer a relevant conceptual framework for building psychological well-being of individuals and communities. The research method employs a library research approach with descriptive-analytical analysis of various primary and secondary sources encompassing classical Islamic literature, contemporary Islamic psychology studies, and empirical research related to mental health in religious contexts. The findings indicate that Aswaja principles have significant correlation with psychological well-being indicators, where moderate and balanced attitudes can prevent extremism that potentially disrupts mental health. The concepts of hifzh al-nafs (preservation of life) and hifzh al-'aql (preservation of intellect) in maqasid al-shariah provide strong theological foundations for integrating spiritual values into mental health interventions. This research concludes that the integration of Aswaja values in mental health promotion programs can create a more comprehensive, contextual, and sustainable approach to improving the psychological well-being of Indonesian Muslim communities.